A construção-suporte no português brasileiro - Flores, Eduardo Almeida (2020)
This work aims to describe the construction-support in Brazilian Portuguese from the perspective of the Grammar of Constructions (GCX). For this purpose, surveys from the database of the Group of Functionalist Studies of the Federal University of Goiás (GEFUFG), concerning the “Fala Goiana” Project and the corpus of the Group of Studies Discourse & Grammar were analyzed. The analyzes are based on studies of Cognitive Linguistics (MINSKY, 1974; LANGACKER, 1987; LAKOFF, 1990; TOMASELLO, 1999; HIMMELMANN, 2004), of the Grammar of Constructions (CROFT, 2001; LANGACKER, 2008; BYBEE, 2010; GOLDBERG, 1995; 2006) and studies of Functional Linguistics Centered on Use (MARTELOTTA, 2011; TRAUGOTT AND TROUSDALE, 2013). It starts from the definition of support-construction as a pairing between form and meaning, consisting of a periphrase, which presents in its prototypical morphosyntactic configuration a verb with a support function and a nominal nucleus with an informational function. This construction integrates a determined hierarchical network and operates, prototypically, in the basic orational organization, at the level of predication, performing the function of predicate. We believe that support construction is part of the linguistic knowledge of speakers and, for this reason, its meaning is related to several cognitive domains and is linked to different conceptual matrices. The support construction represents a cognitive pattern formed in the dynamics of the language and necessary to meet the communicative purposes of the speaker. The results demonstrate that the support construction consists of an abstract cognitive scheme, a formic expression, which instantiates other constructions at the level of subschemas, microconstructions and constructs in the language. The process of formation of this construction occurs through changes in a larger context, at the level of the predication macroscheme. Considering the macroprinciples of linguistic changes, the construction of the support construction cognitive scheme occurs gradually, in small stages, and through general domain cognitive processes, such as analogy. Observing the various uses that codify the support-construction, we verify that it integrates different cognitive domains, such as the time domain, the movement domain, the natural events domain and the health conditions domain.